Validasi Semi Quantitative-Food Frequency Questionnaire terhadap Estimated Food Record untuk Menilai Konsumsi Total Buah dan Sayur pada Mahasiswa - Noviana Ardiyanti; Rian Diana (Jurnal Ilmu Kesehatan dan Gizi, 2025)
College students are in early adulthood, a critical developmental stage marked by physical, psychosocial, and cognitive changes that can significantly impact dietary behaviors, including fruit and vegetable consumption. Adequate intake of fruits and vegetables is essential for maintaining overall health and reducing the risk of non-communicable diseases (NCDs). However, evidence indicates that fruit and vegetable intake among college students often falls below the levels recommended by the World Health Organization (WHO). This study aimed to validate a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) for assessing total fruit and vegetable intake among college students in Surabaya City, Indonesia. A cross-sectional study was conducted involving 30 active university students. The SQ-FFQ method produced higher intake estimates compared to the Estimated Food Record. A statistically significant and strong correlation was found between the two methods (p < 0.001, r > 0.7), indicating strong agreement. These findings support the SQ-FFQ as a valid tool for measuring total fruit and vegetable intake in this population.